Apolipoprotein E gene polymorphisms: a relationship with the risk of coronary artery disease and the effectiveness of lipid-lowering therapy with rosuvastatin - M. I. Churilin; S. I. Kononov; Yu. V. Luneva; Yu. E. Azarova; E. Yu. Klesova; A. V. Kharchenko; S. N. Zhabin; O. Yu. Bushueva; S. V. Povetkin; G. S. Mal; M. A. Solodilova; A. V. Polonikov; et al. (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To analyze the associations of apolipoprotein E (APOE) gene polymorphisms (rs7412 and rs4420638) with the risk of coronary artery disease (CAD) and the effectiveness of lipid-lowering therapy with rosuvastatin.Material and methods. The study involved the analysis of deoxyribonucleic acid samples and phenotypic data of 1700 unrelated individuals of Slavic origin, natives of Central Russia. A pharmacogenetic testing included 205 patients with CAD. Patients were prescribed rosuvastatin with determination of lipid levels and intima-media thickness (IMT) after 6 and 12 months of follow-up.Results. Carriers of the minor T allele for rs7412 polymorphism of the APOE gene were characterized by a lower CAD risk and a higher baseline level of low-density lipoprotein cholesterol (LDL-C). Associations of this polymorphism depended on body mass index. An association with an increased CAD risk was typical for male carriers of the variant G allele for rs4420638 polymorphism of the APOE gene. When treating CAD patients with rosuvas-tatin, a more pronounced lipid-lowering effect on total cholesterol and LDL-C was characteristic of individuals homozygous for the minor T allele for rs7412 of the APOE gene after 1 month of therapy; decrease of the lipidlowering effect with respect to total cholesterol took place in carriers of the heterozygous A/G genotype of rs4420638 polymorphism of the APOE gene after 12 months of therapy. An association was found between the rs7412 polymorphism of the APOE gene and the changes of maximum IMT in CAD patients treated with rosuvastatin. It consisted of the absence of IMT regression in T allele carriers after 6 months of lipid-lowering therapy.Conclusion. Polymorphisms of the APOE gene are associated with parameters of cholesterol metabolism, the risk of CAD and the effectiveness of lipid-lowering therapy with rosuvastatin.